1996
DOI: 10.3109/00016349609055028
|View full text |Cite
|
Sign up to set email alerts
|

The number of follicles and ovarian volume in the assessment of response to clomiphene citrate treatment in polycystic ovarian syndrome

Abstract: Small multiple follicles (> 9) and enlarged ovarian volume (> 6.8 ml) were the most prominent transvaginal ultrasonographic features of ovaries in Clomiphene Citrate nonresponsive patients with polycystic ovarian syndrome. Higher levels of Testosterone, luteinizing hormone and significantly higher number of small follicles were associated with lack of Clomiphene Citrate response. These ultrasonographic features and laboratory assays could be clinically useful for distinguishing better the Clomiphene Citrate no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other investigators have described parameters estimating ovarian response after treatment with clomiphene citrate [2–4]. In one study, greater mean ovarian volume and higher level of LH (which is shown as increased LH/FSH ratio) were associated with a lack of response to clomiphene citrate [3].…”
Section: Characteristic Ovarian Response Parameters Studied In Ovulatmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have described parameters estimating ovarian response after treatment with clomiphene citrate [2–4]. In one study, greater mean ovarian volume and higher level of LH (which is shown as increased LH/FSH ratio) were associated with a lack of response to clomiphene citrate [3].…”
Section: Characteristic Ovarian Response Parameters Studied In Ovulatmentioning
confidence: 99%
“…Other investigators have described parameters estimating ovarian response after treatment with clomiphene citrate [2–4]. In one study, greater mean ovarian volume and higher level of LH (which is shown as increased LH/FSH ratio) were associated with a lack of response to clomiphene citrate [3]. In another, hirsutism (as a manifestation of hyperandrogenemia) and elevated BMI were considered to be good markers predicting resistance to clomiphene citrate [4].…”
Section: Characteristic Ovarian Response Parameters Studied In Ovulatmentioning
confidence: 99%